Analysis of Tea Rhizosphere Bacterial Community at the Seedling Stage Using Terminal Restriction Fragment Length Polymorphism (TRFLP) Techniques - Dwi Ningsih Susilowati; Fani Fauziah; Eko Pranoto; Ernin Hidayat; Mamik Setyowati; Yati Rachmiati (Research Institute for Tea and Cinchona, 2016)
Bio-imunizer contains an active compound ofÂ Chryseobacterium sp. and Bacillus sp. has been developed by PPTK Gambung. This formula has positive effect on the growth of tea plants also potentially increasing resistance of the plant. The purpose of this study was to determine the effects of bacteria in Bio-imunizer to the rhizosphere bacterial communities as well as the consistency of its existence after application on tea plants at the nursery stage. The technique used in this research is Terminal Restriction Fragment Length Polymorphism based on metagenomic and culture dependent approaches. The value of relative abundance, Shannon diversity index, Pielou's evenness index, and Simpson dominance index were calculated. Based on the T-RF profiles of rhizosphere bacterial communities show that Chryseobacterium sp. and Bacillus sp. which is the active compound ofÂ Bio-imunizer consistently found in the tea plant rhizosphere. Application of Bio-imunizer can increase the diversity of rhizosphere bacterial community without affecting the communities that already exist.